PENERAPAN METODE TREND MOMENT DALAM MEMPREDIKSI HARGA MINYAK MENTAH PADA PT ASIAN AGRI - Mujahid, Putra Edi; Gultom, Maju Parsaoran; Lahagu, Hasrat Gideon; Sinaga, Indah (Politeknik Bisnis Indonesia, 2023)
In this research, this study aims to explore the potential and benefits of applying the Trend Moment method in predicting crude oil price trends at PT Asian Agri. The method used is the Trend Moment Method. Based on the results of the evaluation of the trend moment, it can be concluded that the method is good at predicting crude oil prices. With historical data for 2 years. The evaluation value shows that the trend moment value for Adj Close crude oil prices, the value obtained is 1615.65. UMK produces a value of 5079929.413333333. MAPE produces values ​​of 2.698007510149617 and 1.94.